Initial design of an automated system for paddy seedling placement in a germination tray - Mohd Rosli, Muhammad Firdaus; Mahadi, Muhammad Razif; Misri, Muhammad Afiq; Wayayok, Aimrun (Penerbit UTM Press, 2016)
Domestic demand for rice in Malaysia is more than the amount of local production; hence extra supplies are imported from neighbouring countries. For self-sustenance and food security, the government has targeted for a rise in the domestic rice production. Since conventional practice depends on labour, further mechanization is needed in order to achieve the goal. Inspired by the government policy, mechanization system based on System of Rice Intensification (SRI) has been developed and actively researched at the Universiti Putra Malaysia (UPM). One of the efforts is the design of a specialized seedling germination tray, which has been successfully patented. As part of further development program, an automated system for paddy seedling placement is currently developed. The system resembled a conveyor system with instrumentation for controlling the motion and placement of the seeding tray. Based on the result obtained, the conveyor was able to achieve start-stop distance at 16.98 mm if the time-delay variable was set at 100 ms. This paper presents the initial design development of the device. The machine was developed based the specification derived from the tray.